Articular cartilage scores in cranial cruciate ligament‐deficient dogs with or without bucket handle tears of the medial meniscus. Issue 1 (28th November 2016) - Kaufman, Kathryn; Beale, Brian S.; Thames, Howard D.; Saunders, W. Brian
Abstract: Objective: To compare articular cartilage scores in cranial cruciate ligament (CCL)‐deficient dogs with or without concurrent bucket handle tears (BHT) of the medial meniscus. Study Design: Retrospective case series. Animals: Client‐owned dogs treated with arthroscopy and tibial plateau leveling osteotomy or extracapsular repair for complete CCL rupture (290 stifles from 264 dogs). Methods: Medical records and arthroscopic images were reviewed. Medial femoral condyle (MFC) and medial tibial plateau (MTP) cartilage was scored using the modified Outerbridge scale. Periarticular osteophytosis (PAO) and injury to the medial meniscus were recorded. Data were analyzed using Student's t ‐tests, Wilcoxon rank‐sum test, and Fisher's exact test for changes in the stifle based on meniscal condition, body weight, and duration of lameness. Results: PAO, MFC, and MTP articular cartilage scores were not significantly different in dogs with or without BHT. There were no significant differences in MFC or MTP scores when dogs were evaluated based on bodyweight and the presence or absence of a BHT. However, PAO formation was significantly increased in dogs weighing >13.6 kg and concurrent meniscal injury vs. dogs weighing <13.6 kg and concurrent meniscal injury ( P  < .001). Significantly more stifles with chronic lameness (40 of 89; 44.9%) had the highest PAO score of 2 reported compared to only 42 of 182 stifles (23.1%) with acute lameness ( P  < .001). Conclusion: The presence of a BHT of the medial meniscus was not associated with more severe arthroscopic articular cartilage lesions in the medial joint compartment at the time of surgery.